THE CASE STUDY OF THE ESG COSMETIC MARKETING STRATEGY - Lin, Linda Lin-Chin; Chang, Fion Li-Yin (Graduate Program of Universitas Tarumanagara, 2025)
This research would study the Taiwan Environmental Social Governance (ESG) beauty brand -“Pure Plus” (P+) who would use the E-Commerce of marketing strategy in Taiwan cosmetics market to get the revenue target and to be popular and famous. Nowadays, environmental social governance (ESG) has become a global trend, and growing societal urgency towards sustainable development, with companies increasingly acting on sustainability to prove social responsibility. The ESG actions is including E-Commerce, and it is becoming increasingly relevant where companies are leveraging these principles to enhance sustainability, promote ethical practices, and strengthen governance. Therefore, the purpose of this case study would discover the “Pure Plus” (P+) how to use E-Commerce marketing strategy to practice the long-term goal of the sustainable Environmental Social Governance (ESG). This research is adopting a qualitative approach to explore how the “Pure Plus” (P+) company uses E-Commerce marketing strategy to implement ESG goals. P+ is the general agent in Taiwan for a number of world-renowned beauty care and household brands. It is committed to providing customers with safe and reliable health products and reducing the damage of chemical substances to the human body and the global environment. Each product is based on personal experience and intelligent selection, and adheres to the concept of delivering a better and healthy life, sharing with customers pure, healthy and safe high-quality products from all over the world. Love health, love beauty, love sharing and love the earth are the business philosophy of P+. We believe there is no need to compromise between beauty, health and environmental protection. Therefore, P+ is committed to approaching the 17 goals of SDGs from production, packaging to sales. Take the self-developed makeup wipes in 2022 as an example. The material is developed from the internationally recognized biodegradable technology